Schooling, Childhood, and Bureaucracy - Waters, T. author. aut Link
XII, 255 p.
Keywords: In exploring the relationship between bureaucratic schooling and the individual child, Waters describes the persistence of educational inequality, child development, and the nature of bureaucracy. The conclusions point out how education bureaucracies frame both schooling and childhood as they relentlessly seek to create ever more perfect children.